1975
DOI: 10.1007/bf01851184
|View full text |Cite
|
Sign up to set email alerts
|

Protection of the intestinal mucosa during ischaemia by intraluminal perfusion

Abstract: The function of the intestinal mucosa immediately after one hour's ischaemia was examined by means of tests in vivo and in vitro. During the ischaemia, the intestinal loop was perfused with media of different compositions, in an attempt to assess which provided the best protection of the epithelium from the deleterious effects of the ischaemia. The absorption of water, ions and glucose was then monitored in vivo, and the uptake of phenylalanine and beta methyl-glucoside by slices of mucosa was determined in vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

1976
1976
2013
2013

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 7 publications
1
8
0
Order By: Relevance
“…If the mucosa is partially protected by the presence of a glucose-containing buffer in the lumen during the ischaemia, this secretion is either reduced or abolished [25]. In the same way, Triton X-100 treatment leads to an abolition of the absorption of sodium and water, but it does not induce secretion.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…If the mucosa is partially protected by the presence of a glucose-containing buffer in the lumen during the ischaemia, this secretion is either reduced or abolished [25]. In the same way, Triton X-100 treatment leads to an abolition of the absorption of sodium and water, but it does not induce secretion.…”
Section: Discussionmentioning
confidence: 94%
“…In contrast, following treatment with Triton X-100, the number of mature enterocytes remaining on the sides of the villi is presumably sufficient to maintain active transport at a finite, albeit reduced level. An analogous situation arises when the mucosa is protected from the deleterious effect of ischaemia by introduction of a glucose-containing buffer into the lumen during the trauma; under such conditions, active transport in vitro and glucose absorption in vivo are both reduced but not abolished [25,31]. One other point is worth mentioning in this context, viz., that it has recently been deduced from experiments on rat intestine that any cells apparently intact on the sides of the villi after acute ischaemia may be functionless because of the depletion of their energy supplies during the ischaemic period [22]; such considerations would presumably not apply to intestines treated with Triton X-100.…”
Section: Discussionmentioning
confidence: 98%
“…Finally, we have shown in previous stud ies [12,13,18] that the deleterious effects of ischaemia in the small intestine can be miti gated by intraluminal perfusion during the trauma, and have demonstrated that the oxy gen content of the luminal fluid is the most important factor in this protection. In the present work, we see that simply rinsing out the colon before the intervention has little effect on the functional status of the isch aemic organ; on the other hand, if the organ is perfused with an oxygenated buffer during the ischaemia, the functional capacity of the colonic mucosa is seen to be perfectly normal when determined in vitro 1 h after the end of the trauma (table II), though clearly, as pointed out above, much of the normaliza tion probably occurs during the post-ischaemic perfusion.…”
Section: Discussionmentioning
confidence: 99%
“…As in the small intestine ------------------------------------------------------ [12,19], the net absorption of water and elec trolytes across the normal mucosa is trans formed after this trauma into net loss across the ischaemic bowel. However, detailed ex amination of the functional characteristics of the two canine intestines gives rise to inter esting questions concerning the source of this fluid.…”
Section: Discussionmentioning
confidence: 99%
“…was used and the duodenum was perfused with isotonic NaHCO3. The In the dog, severe mucosal desquamation occurs after an ischaemia of 1 hr, but the effects can be mitigated by intraluminal perfusion during the ischaemic period (Mirkovitch, Menge & Robinson, 1975). One of the factors aiding in this protection is the oxygen content of the perfusate (Robinson & Mirkovitch, 1977).…”
Section: Pmentioning
confidence: 99%